Fundamental methods of mathematical economics - Chiang, Alpha C. (Auckland : McGraw-Hill, 1984)
The book introduces one to the basic mathematical methods that have become indispensable for a proper understanding of the current economic literature.
Includes index.
rua 17/04/15
Loans
Keywords: Economics, Mathematical; Mathematical methods